2020
DOI: 10.1088/1755-1315/521/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Post puerulus of scalloped spiny lobster, Panulirus homarus (Linnaeus 1758) rearing in floating net cage with different artificial diet

Abstract: Scalloped spiny lobster (Panulirus homarus) is an export commodity and high economic value in Asian-Pacific markets. The purpose of this study was to determine the best artificial feed for scalloped spiny lobster nursery in floating net cage. The nursery was conducted using 9 floating net cage 1 × 1 × 1 m in size with three treatments and 3 replicates. Three different artificial diets were used as treatments, i.e.: A, commercial pellet for grouper, with higher protein level (53.56%) but lower stability, less d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
2
Order By: Relevance
“…The use of energy derived not from feed but obtained from consuming peers is suspected to be an additional energy source that supports growth. FCR values from this study showed values that were the differ as the results of Slamet et al, (2020) research, namely the FCR values of lobsters fed artificial feed ranged from 3.0-3.20.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 80%
See 1 more Smart Citation
“…The use of energy derived not from feed but obtained from consuming peers is suspected to be an additional energy source that supports growth. FCR values from this study showed values that were the differ as the results of Slamet et al, (2020) research, namely the FCR values of lobsters fed artificial feed ranged from 3.0-3.20.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 80%
“…Figure 6 shows that the highest average live survival value of scalloped spiny lobster was found in the P1 treatment with a value of 100%, followed successively by the P2 treatment of 75%, P3 of 67% and the lowest survival value was found in the P4 treatment with a value of 58%. In general, the percentage of survival rate in this study was higher than that of Slamet et al, (2020), which ranged from 16.7% -39% for 120 days of lobster rearing. The results of the analysis of variance showed that the results of adding chicken egg hatching waste to granulated lobster feed had a real effect on the survival of scalloped spiny lobter.…”
Section: Survival Rate (Sr)contrasting
confidence: 52%
“…Lobsters in grow-out net cages mainly used trash fish for feed. Other fresh feeds are crustaceans and mollusks [8]. From this feeding habit, spiny lobsters are characterized as opportunistic carnivores, which utilize high protein, low lipid, and moderate to high levels of carbohydrates food as their main feed [9].…”
Section: Introductionmentioning
confidence: 99%
“…The development of lobster puerulus... (Ishaaq Saputra) are abundant in certain Indonesian waters (Chan, 2019;Setyanto et al, 2019;Priyambodo et al, 2020). Lobster farmers have been cultivating them for decades in small quantities using traditional methods by feeding them trash fish, but research on the development of prepared diets continues to progress (Kurnia et al, 2017;Marchese et al, 2018;Ridwanudin et al, 2018;Amali & Desi, 2020;Arumugama et al, 2020;Prayitno et al, 2020;Nankervis & Jones, 2022). It has been reported that lobster juveniles can achieve market size after nine months of post metamorphic culture.…”
Section: Introductionmentioning
confidence: 99%